An Analysis of Students’ Grammatical Errors in Writing Descriptive Texts at Senior High School Level - Lidia Natalia Lumban Gaol; Yenita Br Sembiring; Elita Modesta Br Sembiring (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates the grammatical errors made by tenth-grade students in writing descriptive texts at SMK Telkom Medan. Adopting a descriptive qualitative approach, the research aimed to identify the types and sources of grammatical errors found in students’ writing. The data were collected through students’ written tasks and analyzed using the Surface Strategy Taxonomy by Dulay, Burt, and Krashen (1982), which classifies errors into omission, addition, misformation, and misordering. The findings revealed that misformation was the most frequent error (40.2%), followed by omission (33.7tc%), addition (16.8%), and misordering (9.2%). In terms of error sources, intralingual transfer was the dominant factor, indicating students’ overgeneralization of grammatical rules. Other sources included interlingual transfer, context of learning, and communication strategies. The results highlight the need for more targeted grammar instruction and feedback in EFL writing classes. This study contributes to improving grammar pedagogy and promoting more effective teaching strategies in descriptive writing instruction.